Death-related distress in adult primary brain tumor patients. Issue 5 (10th April 2020) - Loughan, Ashlee R; Aslanzadeh, Farah J; Brechbiel, Julia; Rodin, Gary; Husain, Mariya; Braun, Sarah E; Willis, Kelcie D; Lanoye, Autumn
Abstract: Background: A diagnosis of cancer may increase mortality salience and provoke death-related distress. Primary brain tumor (PBT) patients may be at particular risk for such distress given the certainty of tumor progression, lack of curative treatments, and poor survival rates. This study is the first to examine the prevalence of death-related distress and its correlates in PBT patients. Methods: Adult PBT patients (N = 105) enrolled in this cross-sectional study and completed the Death Distress Scale (subscales: Death Depression, Death Anxiety, Death Obsession), Generalized Anxiety Disorder–7, and Patient Health Questionnaire–9. Prevalence and predictors of death-related distress, and the relationships of demographic variables to clusters of distress, were explored. Results: The majority of PBT patients endorsed clinically significant death-related distress in at least one domain. Death anxiety was endorsed by 81%, death depression by 12.5%, and death obsession by 10.5%. Generalized anxiety was the only factor associated with global death-related distress. Cluster analysis yielded 4 profiles: global distress, emotional distress, resilience, and existential distress. Participants in the resilience cluster were significantly further out from diagnosis than those in the existential distress cluster. There were no differences in cluster membership based on age, sex, or tumor grade. Conclusions: PBT patients appear to have a high prevalence of death-related distress, particularly death anxiety. Further, 4 distinct profiles of distress were identified, supporting the need for tailored approaches to addressing death-related distress. A shift in clusters of distress based on time since diagnosis also suggest the need for future longitudinal assessment.